Avaliação da qualidade da silagem de milho inoculada com Lactobacillus buchneri - Carneiro, Felipe (2016)
Corn is the most traditional fodder and used by growers to present optimal conditions for producing good silage, taking into consideration that the quality of silage, and the nutritional requirements of the plants, are determined by the amount of nutrients to the plant extracts during their cycle. This work aimed to evaluate the quality and production of corn silage after cultivation of winter pastures with the use of inoculant in silage, in a livestock farming system integration. The experimental area used was 7 hectares where corn was sown Agroeste 1572 PRO. Harvesting and ensiling of corn grain occurred when the dough reached the stage represented by dialing 2/3 of the grain delimiting two-thirds milk line which corresponds to percentage of starch deposition in grain, having an average content of material dried ranging from 32% to 35%. The silage was stored in micro silos made of PVC tubes with sealing the ends and they remained closed for 60 days, to occur a good quality brew. The experimental design was completely randomized with split plot in time, the main plot corn silage had three silos with use of biological inoculant (Lactobacillus buchneri) and three silos control without inoculant, subplot day closing time 0 and day 60 . the inclusion of inoculant species of heterofermentative bacteria Lactobacillus buchneri in corn silage did not significantly alter the material ensiled forage due to incompatibility of the fermentation of the inoculated strain. The values found for MS, CP, N, P, K silage were not positively influenced by inoculation with Lactobacillus buchneri nor the silo closing time.